Performance enhancement in the workplace: why and when healthy individuals should disclose their reliance on pharmaceutical cognitive enhancers - Garasic, Mirko D.; Lavazza, Andrea (Frontiers in Systems Neuroscience, 2015)
The use of pharmaceuticals cognitive enhancers (PCE) has been stirring growing interest, not only in the scientific domain but also in the popular media, and has probably had some increase recently in academic, professional and military quarters. So this phenomenon is deemed as a normal procedure aimed at improving the performance of an individual as well as the overall standards of an organization. Although the vast majority of countries have some kind of restrictions to reduce the wide non-medical usage of PCE, these can be overcome quite easily. In arguing for our explicit claim that, in many contexts, the use of cognitive enhancers should be disclosed—as a moral and socially relevant duty—we maintain that PCE present typical, or at least not rare, properties. The features are the following: (a) the enhancer has acute and/or chronic effects. In the first case, shortly after taking the drug the performance is significantly better than average; in the second case, there is a growing or lasting effect, which, however, is poised to diminish when one stops taking the drug; (b) those effects are significant (there is a difference in the outcome considered between taking and not taking the drug) and sometimes dramatic; and (c) a third feature, not directly related to enhancers as such, is their varying safety, availability, and legal permissibility, which might either induce people to take them or refrain them from doing so. We will consider the issue of fairness due to “unenhanced” people as well as the potentially dysfunctional social consequences of an undisclosed PCE use.